Microbial lipid production from food waste saccharified liquid and the effects of compositions - Ma, Xiaoyu (2020)
The residues of food waste after removing waste cooking oils could be converted to microbial lipid by oleaginous yeasts and microbial lipid could be used as a raw material of biodiesel with waste cooking oils. This process would have positive environmental and economic benefits. However, the composition of food waste is extremely complex. Many types of organic acids, such as lactic acid and acetic acid, could be accumulated during the collection, transportation and storage processes. The effects of these substances on microbial lipid production remained unknown. In this study, food waste saccharified liquid (FWSL) without any additional nutrients was fed to Rhodosporidium toruloides 2.1389 for microbial lipid production. Total biomass concentration, lipid concentration and lipid yield increased by 87.4%, 69.4% and 69.3%, respectively, compared with the YPD medium. Remarkably, increasing the concentration of lactic acid in the medium promoted the total biomass concentration of yeast. Furthermore, lipid concentration decreased slightly when single lactic acid or single acetic acid concentration was below 5 g/L or 1 g/L in the culture media. Metal elements that were present in the medium had considerable synergistic effects on lipid production. When four metal elements (i.e. Mg, Ca, Na and K) were present in the medium, total biomass concentration, lipid concentration, lipid content and lipid yield increased by 22.01%, 33.51%, 9.43% and 33.33%, respectively, compared with those in the control group. The interaction among the FWSL compositions that led to the promotion of microbial lipid production was beyond the inhibition effect. The engineering implication analysis evidently suggested that the process of microbial lipid production from FWSL was economically feasible and had potential industrial application prospects.